ANTECEDENT VARIABLES, AUDIT REVIEW INTEGRATION COMPETENCY AND AUDIT EXCELLENCE: AN EMPIRICAL INVESTIGATION: ตัวแปรที่มาก่อน สมรรถนะในการบูรณาการการสอบทานการสอบบัญชีและ ความเป็นเลิศในการสอบบัญชี: การตรวจสอบเชิงประจักษ์ - Phosrichan, Nittaya; Boonlua, Sutana; Janjarasjit, Suparak (Journal of Graduate School of Commerce-Burapha Review, 2018)
ABSTRACT The research purpose is to examine the association among antecedents (modern audit vision, audit experience value, audit knowledge achievement, information technology readiness, and stakeholder expectation), audit review integration competency and audit excellence. This research emphasized audit review integration competency on the monitoring and assessing of processes with a criteria of audit process that is scheduled as planned. This research attempts to integrate the key elements of the performance review audit for five new dimensions. The 398 samples were selected from Certified Public Accountants (CPAs) in Thailand. A questionnaire was used for collecting the data. The response rate was 22.50%. The results of regression analysis show that the antecedents variables have a significant positive relationship with audit review integration competency. Similarly, the audit review integration competency have significant positive impacts on audit excellence. บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อตรวจสอบความสัมพันธ์ในกลุ่มของสมรรถนะในการบูรณาการการสอบทานการสอบบัญชี ผลลัพธ์ที่ตามมา และความสำเร็จในการสอบบัญชี งานวิจัยนี้มุ่งเน้นที่สมรรถนะในการบูรณาการการสอบทานการสอบบัญชีเกี่ยวกับกระบวนการตรวจสอบ และประเมินเกี่ยวกับเกณฑ์ของกระบวนการสอบบัญชีที่เป็นไปตามแผนการสอบบัญชีที่กำหนดไว้ งานวิจัยนี้พยายามบูรณาการองค์ประกอบที่สำคัญของสมรรถนะในการสอบทานการสอบบัญชีสำหรับ 5 มิติใหม่ เลือกกลุ่มตัวอย่างจากผู้สอบบัญชีรับอนุญาต (CPAs) ในประเทศไทยจำนวน 398 คน ใช้แบบสอบถามในการเก็บรวบรวมข้อมูล อัตราการตอบแบบสอบถาม คือ 22.50% ผลของการวิเคราะห์การถดถอย แสดงให้เห็นว่าตัวแปรที่มาก่อน มีความสัมพันธ์เชิงบวกอย่างมีนัยสำคัญกับสมรรถนะในการบูรณาการการสอบทานการสอบบัญชี ในทำนองเดียวกัน สมรรถนะในการบูรณาการการสอบทานการสอบบัญชีก็มีผลกระทบเชิงบวกอย่างมีนัยสำคัญต่อความเป็นเลิศในการสอบบัญชี